Possible constitutive equations of micropolar solids (Archives of Mechanics - Test, 2001)
Recently the micropolar continuum is used for investigation of some problems of solids. There exist several theories of micropolar continuum; We will study two types of them. The simplest one is Cosserat's continuum while the Eringen's model is more complicated. If the solid is not elastic then the constitutive equations are not generally known. In the paper, a method will be shown for the determination of possible constitutive equation in case of inelastic solids.